A Taxonomic Study of the Genus Blastus Lour. (Melastomataceae) in Vietnam - Hien, Nguyen Thu; Xuyen, Do Thi; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: The genus Blastus Lour. belongs to the family Melastomataceae with 12 species over the World [ 1 ], among which five are found in Vietnam [ 2 , 3 ]. Previously, there have been some studies on this genus in Vietnam. The first study documented the genus Blastus was the “Flora Cochinchinensis” by Loureiro (1790) [ 4 ] . To date, there have been data of five species and one variety of Blastus in Vietnam, among them one species and one variety may be endemic to Vietnam, which are Blastus eglandulosus and B. boneensis var. eberhardtii . In this article, we provided the diagnostic characteristics of the Blastus species found in Vietnam, provided some information about distribution, ecology, biology and the identification key to these five species and one variety. Keywords: Blastus , Melastomataceae, taxonomy, Vietnam.